Features of Engineering and Development Implementation to Increase the Efficiency of Ukraine Innovative Transformations (Economics and region, 2021)
The study identified that the most effective organizational structure of the modern combination of advanced science, advanced production systems and technologies, commercialization and competitiveness of innovation is the creation of high-tech research and production systems (HRPS) in Ukraine. Analogs of these systems are such successful global companies as Boeing, BMW, Sony, Samsung and many others, which are integrated into a single system of research (engineering), manufacturing, commercial, development and other departments. It is proved that for effective work and achievement of competitive results the modern HRPS should include: coordination and scientific and technical councils, divisions on strategic researches, forecasting and planning; engineering departments that form the basis of scientific and technical centers (STC); effective financial, marketing, development and other institutions; extensive and flexible infrastructure. In the process of research and in the article the following are determined: rational-organizational structure and functions of STC; the content and sequence of development and implementation of "turnkey" programs for the HRPS development; the essence of branded and lifelong service of unique innovative objects. The implementation of the developed proposals will accelerate the transition of domestic enterprises to world standards of management and continuous innovation and high-tech progress, as well as: reduce the complexity of work and duration of programs; reduce operating costs; reduce the total cost of programs; significantly increase the quality and competitiveness of domestic innovative developments and their manufacturers.
Keywords: engineering; innovative transformations; research and production systems; development; науково-виробничі системи